The Most Popular Fantasy Novel in the Beginning of Twenty- First Century ‘Harry Potter’ - Farhan Alsharab, Osama (International Journal of English Literature and Social Sciences (IJELS), 2019)
Harry Potter is a series written by J. K. Rowling which belongs to the fantasy literature genre. The series contains seven books, the first of which was published in 1997. Each of the Harry Potter stories has an independent plot. The story about an orphan boy. At one year of age, he loses his parents, who are murdered by the dark wizard. This study aims to investigate the factors behind the popularity of Harry Potter by J. K. Rowling as popular culture. To discover the main reasons driving the enormous worldwide popularity of this work, this study offers a literary analysis of Harry Potter by J. K. Rowling as a contemporary fantasy text which has been one of the most famous in the two decades preceding the writing of this paper. The research focusing on the important elements such as settings, characters, plot, themes, and the narrative structure and language to figure out factors behind the wide acceptance of Rowling’s work. The research findings show that there are many factors behind putting this fantasy text in its position as a pop. culture phenomenon. For example, the elements of the story shaped in such a way to be more attractive. The technological development in the postmodern era also has significant importance within the success of Harry Potter.